2016
DOI: 10.1111/hepr.12780
|View full text |Cite
|
Sign up to set email alerts
|

Muscle volume loss as a prognostic marker in hepatocellular carcinoma patients treated with sorafenib

Abstract: Muscle wasting is an important prognostic factor in patients treated with sorafenib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
118
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(131 citation statements)
references
References 31 publications
8
118
3
2
Order By: Relevance
“…This result indicated that these malnutritional factors were important for the survival of patients with HCC treated with sorafenib. Several recent reports indicated that decreased skeletal muscle mass was an important prognostic factor in patients with chronic liver disease and HCC (2,3,5,6). These results suggested that preventing reductions in skeletal muscle thickness may improve the OS of patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This result indicated that these malnutritional factors were important for the survival of patients with HCC treated with sorafenib. Several recent reports indicated that decreased skeletal muscle mass was an important prognostic factor in patients with chronic liver disease and HCC (2,3,5,6). These results suggested that preventing reductions in skeletal muscle thickness may improve the OS of patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, an increasing number of studies have demonstrated that sarcopenia may affect the clinical state of patients with liver disease (1)(2)(3). Moreover, skeletal muscle wasting assessed by CT has been reported to be a prognostic marker for patients with hepatocellular carcinoma (HCC) treated with sorafenib (5,6). In those reports, skeletal muscle mass was usually measured by imaging modalities, such as CT and magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Although sarcopenia has been reported to be an independent predictor of survival in patients with various cancers including HCC [11-15], there have been only three studies on HCC patients treated with sorafenib [16-18]. However, there have been no studies focusing on both skeletal muscle and visceral fat in HCC patients treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, sarcopenia has been reported to be an independent predictor of survival in patients with lung, gastrointestinal, pancreatic, and colorectal cancer as well as HCC [11-15]. For HCC patients receiving sorafenib therapy, it has been reported that skeletal muscle depletion is an independent prognostic factor [16-18]. However, visceral fat area (VFA) is a controversial topic regarding its effects on survival of patients with HCC [15, 19-21].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Its presence has also been associated with increased toxicity in patients with HCC treated with sorafenib 16 and reduced survival, but the few data available come mainly from oriental series, where ethnic and anthropometric differences limit reproducibility in a Western setting. [17][18][19] Only one Western study is available, with a limited number of patients treated with various tyrosine kinase inhibitors. 20 The aim of the present study was to identify the prevalence and influence of sarcopenia in a homogeneous population of European Caucasian patients with advanced HCC undergoing sorafenib therapy.…”
Section: Introductionmentioning
confidence: 99%